Penguat Jembatan dengan Untai Pembalik Fase - Murtianta, Budihardja; Sari, Erlina (Elektrika, 2022)
The maximum output voltage of the audio amplifier is limited to the magnitude of the power supply voltage of the power transistor or the operational amplifier on the final amplifier. This limits the maximum power of the audio amplifier output. The way to enlarge the output power of the audio amplifier without increasing the voltage is the bridge method or bridged modes. With this method a bridge amplifier will be generated. This Bridge Amplifier is also known as Bridge-Tied Load (BTL) or Bridged Transformerless. The principle of Bridge Amplifiers is to use a pair of final amplifiers whose outputs have opposite phase each other. There are 3 ways to make a pair of power amplifiers have opposing phases: with internal modification, with an audio transformer (phase splitting audio input transformer) and with a simple active phase reversal splitter circuit). This paper will discuss Bridge Amplifiers with simple phase inverting circuits. A pair of audio power amplifiers using two TDA2050 chips which are operated at ± 19 Volt supply voltage. The phase inverting circuit using IC TL072. Sinusoidal signal with an amplitude of 200 mVp and a frequency of 1 KHz is used as an input signal. The results to be observed and measured are gain, input, output and bandwidth of the bridged amplifier compared to the usual amplifier